2021
DOI: 10.3390/ani11020397
|View full text |Cite
|
Sign up to set email alerts
|

Genomics Analysis of Bacillus megaterium 1259 as a Probiotic and Its Effects on Performance in Lactating Dairy Cows

Abstract: In this study, we isolated a novel bacterium, Bacillus megaterium 1259 (BM1259), from chicken manure. Whole-genome sequencing analysis showed that the BM1259 complete genome is composed of a 5,043,095 bp circular chromosome and three circular plasmids, and it encodes 5379 coding genes and 182 RNA genes. Among these genes, a series of nitrate assimilation-related genes and pathways were identified, implying a potential role of BM1259 in nitrate metabolism. In addition, 24 lactating Holstein dairy cows were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Ding et al found that the C2:C3 could be significantly reduced and both the TVFA and C3 content could be increased with supplementation of bacillus subtilis in the fermentation test [ 37 ]. However, our results demonstrated that after the addition of BM1259, the C2 concentration increased significantly and the C2:C3 increased, indicating that the rumen fermentation type changed to acetate fermentation, which was consistent with the significant increase in the content of Saccharofermentans in our previous study [ 2 ]. The levels of NH 3 -N and H 2 S in the urine not only affected the health of the livestock and humans, but also reflected the nitrogen utilization capacity of animals [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ding et al found that the C2:C3 could be significantly reduced and both the TVFA and C3 content could be increased with supplementation of bacillus subtilis in the fermentation test [ 37 ]. However, our results demonstrated that after the addition of BM1259, the C2 concentration increased significantly and the C2:C3 increased, indicating that the rumen fermentation type changed to acetate fermentation, which was consistent with the significant increase in the content of Saccharofermentans in our previous study [ 2 ]. The levels of NH 3 -N and H 2 S in the urine not only affected the health of the livestock and humans, but also reflected the nitrogen utilization capacity of animals [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, research and application of microecologics has attracted extensive attention from scholars in domestic fields and abroad. As a new kind of green and environmental protection feed additive, microecologics have been widely used in animal husbandry due to its green, safe, and residue-free function, which can be used to replace antibiotics, to promote the healthy growth of animals, and improve the environment [ 1 , 2 ]. At present, lactic acid bacteria, bacillus, yeast, photosynthetic bacteria, and so on are the most widely studied microecological additives.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bacillus megaterium was the most dominant population in the SB silage. Bacillus megaterium is a facultative anaerobic Gram-positive bacterium that can secrete antimicrobial compounds ( Rajabi et al, 2020 ) and is widely used as a probiotic inoculant in the silage and feed industry ( Deng et al, 2021 ). Some Bacillus species could increase the lactic acid concentration and improve the aerobic stability of silage ( Lara et al, 2016 ; Bai et al, 2020 ) by producing antimicrobial substances.…”
Section: Discussionmentioning
confidence: 99%
“…А positive effect was achieved in the treatment of SM in cows without the use of antibiotics by introducing the probiotic B. megaterium NCH 55 into the diet. This effect was primarily expressed in an increase of the average daily milk yield by 32.2% on the 30 th day of the experiment (20). Another indication of this effect was the decrease of SCC in the experimental group from 290.00±32.12 to 96.80±39.03 ths/cm 3 which was similar to the control group.…”
Section: Discussionmentioning
confidence: 65%